Peningkatan Keterampilan Menganyam pada Materi Seni Rupa dengan Penerapan Model Pembelajaran Visualization, Auditory, and Kinesthetic (VAK) Pada Siswa Kelas V SD Negeri 1 Bumirejo Tahun Ajaran 2023/2024 - Annisa Fajar Rahmawati; Rokhmaniyah Rokhmaniyah; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2024)
The study aimed to improve weaving skills in Fine Arts by implementing the Visualization, Auditory, and Kinesthetic (VAK) learning to fifth grade students of SD Negeri 1 Bumirejo. It was collaborative classroom action research conducted in three cycles. Each cycle consisted of planning, implementation, observation and reflection. The subjects were 23 fifth grade students of SD Negeri 1 Bumirejo in academic year of 2023/2024. The data collection techniques were observation, interviews and tests on teacher and students. Data validity used triangulation of techniques. The analysis techniques were qualitative and quantitative. It was collaborative classroom action research conducted in three cycles and five meetings. Each cycle consisted of planning, implementation, observation, and reflection. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and tests. Data validity used triangulation of techniques and triangulation of sources. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results indicated that the Visualization, Auditory and Kinesthetic learning improved weaving skills. The percentages of passing grades on the process increased 8.5% from 91.5% in the first cycle to 100% in the second cycle and remained 100% in the third cycle. The percentages of passing grades on students' weaving skills improved 6.5% from 87% in the first cycle to 93.5% in the second cycle, and 100% in the third cycle which increased 6.5% from second cycle. It concludes that the Visualization, Auditory, and Kinesthetic (VAK) learning improves weaving skills in Fine Arts to fifth grade students of SD Negeri 1 Bumirejo in academic year of 2023/2024.